Fluid overload in patients undergoing TAVR: what we can learn from the nephrologists - Nitsche, Christian (ESC Heart Fail, 2021)
AIMS: Fluid overload (FO) puts aortic stenosis (AS) patients at risk for heart failure (HF) and death. However, conventional FO assessment, including rapid weight gain, peripheral oedema, or chest radiography, is inaccurate. Bioelectrical impedance spectroscopy (BIS) allows objective and reproducible FO quantification, particularly if clinically unapparent. It is used in dialysis patients to establish dry weight goals. BIS has not been tested for prognostication in AS. This study aimed to evaluate whether BIS adds prognostic information in stable patients undergoing transcatheter aortic valve replacement (TAVR). METHODS AND RESULTS: Consecutive patients scheduled for TAVR underwent BIS in addition to echocardiographic, clinical, and laboratory assessment. On BIS, mild FO was defined as >1.0 L and severe as >3.0 L. Combined HF hospitalization and/or all‐cause death was defined as primary endpoint. Three hundred forty‐four patients (81.5 ± 7.2 years old, 47.4% female) were prospectively included. FO by BIS was associated with clinical congestion signs, higher serum markers of cardiac injury, poorer left ventricular function, higher pulmonary pressures, and more severe tricuspid regurgitation (all P < 0.05). Yet, clinical examination was unremarkable in >30% in mild FO, only detected by BIS. During 12.1 ± 5.5 months, 67 (19.5%) events were recorded (40 deaths, 15 HF hospitalizations, and 12 both). Quantitatively, every 1 L increase in FO was associated with a 24% (HR 1.24, 95% CI 1.13–1.35, P < 0.001) increase in event hazard. This association persisted after adjustment for STS/EuroSCORE‐II, NT‐proBNP, left ventricular ejection fraction, and renal function. CONCLUSIONS: In patients undergoing TAVR, FO by BIS is strongly associated with adverse outcomes. BIS measurement conveys prognostic information not represented in any currently used AS/TAVR risk assessments.